Hydrological characteristics of groundwater in the Nam Dinh area from isotopic results - Hoan, Hoàng Văn; Nhân, Phạm Quý; Nhận, Đặng Đức; LARSEN, FLEMMING; FRANK, WAGNER; PURTSCHERT, ROLAND; GERBER, CHRISTOPH (Vietnam Journal of Earth Sciences, 2014)
This paper presents the results of isotopic hydrogeological studies in the years from 2010 to 2012 to evaluate the hydraulic system and the change of the hydraulic relationship between aquifers in Nam Dinh Province. Using isotopes of water such as Deuteri (2H), Oxygen 18 (18O), Tritium (3H) and the Carbon 14 (14C) in the total dissolved inorganic carbon (DIC), Argon 39 (39Ar) dissolved in water. The relationship between the stable isotopic composition of water (δ2H and δ18O) as well as the age of the water in the aquifers, which allows to come to the conclusion that the regional aquifers are hydraulic interrelated to each other and fresh water lens of Pleistocene aquifer in the southeastern of Nam Dinh province is provided by the Neogen and Triassic fractured and karstic aquifers, in the northwest. Hydraulic relationship between the aquifers in the study area changes with seasons, including changes in the hydraulic relationship between surface water, sea water, and the change in the Holocene aquifer is stronger than Pleistocene, Neogen and Triassic aquifers. Groundwater in the depth from 43m to 168.6m below ground surface have hydraulic relationship with each other. Based on the age by radioactive isotopes 14C and 39Ar/40Ar isotopic ratios and 3H in the water samples it had been determined that groundwater flow direction of the Pleistocene aquifer, Neogen and Triassic is from Northwest to Southeast.